2019
DOI: 10.1007/s42452-019-1039-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of nano-volcanic scoria in the concrete binder

Abstract: The objective of this study is to investigate the efficiency of volcanic scoria when added to the concrete binder at a nano-scale. Nano volcanic scoria (nano-VS) was obtained by grinding a local volcanic scoria for 6 h. Twenty-four concrete mixes with four w/b ratios (0.4, 0.5, 0.6 and 0.7) and six-replacement levels of nano-VS (0%, 1%, 2%, 3%, 4%, and 5%) have been produced. The investigated concrete properties were the compressive strength, the water penetration depth, the concrete porosity and the chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…GO nanosheets were synthesized using a modified Hummers' method 55,56 . Our previous study confirmed that GO flake thickness was approximately 1.25 nm, composed of two stacked individual monatomic GO layers 50 . After DTT modified on GO nanosheets, the thickness of t-GO nanosheets was increased to around 2 nm, speculating that more layers were stacked together (Figure 2a).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…GO nanosheets were synthesized using a modified Hummers' method 55,56 . Our previous study confirmed that GO flake thickness was approximately 1.25 nm, composed of two stacked individual monatomic GO layers 50 . After DTT modified on GO nanosheets, the thickness of t-GO nanosheets was increased to around 2 nm, speculating that more layers were stacked together (Figure 2a).…”
Section: Resultssupporting
confidence: 67%
“…The GO nanosheets, as the polymer reinforcement, can endow composite materials with high strength and superior ductility 47,48 , but the aggregation of GO nanosheets in polymer solution can cause the decrease of cytocompatibility of hydrogels. Such aggregation could be improved by grafting some molecules, such as DL-dithiothreitol (DTT), the dispersion of GO nanosheets in a polymer network could be also ameliorated, and the related properties could be further improved 49,50 . the pNHG hydrogel with interpenetrating networks could be formed increasing the temperature above LCST due to the interaction between the pNiPAM, HECS, and t-GO nanosheets, and the gelation mechanism was displayed.…”
Section: Intruductionmentioning
confidence: 99%
“…Compressive strength of the samples and the statistical evaluation of the strength of the series are shown in the Table 8. Previously the pozzolanic activity of mineral additives was assessed by the method of lime absorbing [10]. Summary data are given in Table 9.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, studies were conducted to study of physical and mechanical properties of volcanic rocks in this region and volcanic rocks based concretes. Currently, there is a significant increase in interest in deposits of volcanic slag as a relatively low-energy-intensive building material with high thermal protection properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [37][38][39][40][41] added a certain amount of nano-siO 2 to concrete to improve the durability of concrete. Al-Swaidani [42] studied the efficiency of adding concrete binder to volcanic slag on a nanometer scale. In recent years, a new method for producing heterogeneous photocatalysts, a high-energy ball milling method, has been proposed.…”
Section: Introductionmentioning
confidence: 99%